EFFICIENCY ENHANCEMENT AND REDUCING LOGISTICS COST WITH MATHEMATICAL MODEL OF AUTO PART INDUSTRY A CASE STUDY: P.E TECHNIC CO., LTD. IN PHITSANULOK PROVINCE - Khanongnuch, Thanida; Muangwai, Alongkorn (Life Sciences and Environment Journal, 2021)
This research proposes a reduce logistics cost for production of Finite Capacity Scheduling (FCS) System for assembly flow shop with multiple common due dates. The proposed FCS system is a two-step procedure. Firstly, it uses hierarchical dispatching rules to sequence the Jobs. Secondly, a linear programming model is used to determine the optimal start time of each operation to minimize total costs of tardiness penalty, holding cost of finished goods and work-in-process, and changeover cost, considering finite capacity of all work centers and precedence constraints of operations. A case study using real industrial problem is conducted to demonstrate the performance of the proposed FCS system. The results show that all levels of the hierarchical dispatching rules significantly affect the scheduling performances. The LP approach can effectively determine optimal start time of each operation to get the optimal schedule based on the sequence of Jobs generated from the hierarchical dispatching rules. Moreover, the best sequence of Jobs generated from the hierarchical dispatching rules is at least local optimal since when it is modified by local search methods, its performance cannot be improved.